The Satisfaction Level of Fifth-Grade Teachers Regarding the Prevailing School Climate during the Assessment of Acquired Skills Examination A Field Study in Primary Schools in the City of M’sila - DAKHOUCHE, Mabrouk; TAABLI, Mohamed Tahar (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2024)
The present study aimed to uncover the level of satisfaction of fifth grade primary school teachers about the prevailing school climate during the examination for assessing the attainments of the primary education stage in the city of M'sila's schools. It also examined whether there were differences among them in the level of satisfaction due to variables (gender, specialization, work system in the school, and professional experience). To do so, the researcher adopted the descriptive approach and designed a questionnaire for this purpose. He presented it to a group of arbitrators from different universities. After making the modifications suggested by the arbitrators, the questionnaire was applied to a prospective sample of 30 teachers to verify its psychometric properties. Its reliability was first confirmed by calculating Cronbach's alpha coefficient and the split-half coefficient. Its validity was secondly confirmed by calculating the internal consistency validity and construct validity. The final version of the tool consisted of 39 statements distributed over five dimensions: relationships and communication, psychological support, school environment (spaces, facilities and means), content and conditions of the exam, and training. The tool was applied to the main research sample. After processing and analyzing the data, the researcher found that the level of satisfaction of fifth grade primary teachers about the prevailing school climate during the assessment exam of acquired knowledge was moderate. There were no statistically significant differences in the level of satisfaction according to the variables of gender, specialization, and work system in the school. However, there were significant differences in the level of satisfaction among teachers according to the variable of professional experience between those with less than 10 years of experience and those with more than 20 years of experience, in favor of the latter group. Based on the study's results, the researcher recommended some procedures and suggestions to improve the school climate and develop the exam in line with the most advanced global practices in educational evaluation.